Applicability of a serodiagnostic line blot for idiopathic inflammatory myopathy: the muscle biopsy is not all - Fontana, Pedro Nogueira; da Silva, Vinícius Gomes; Corazzini, Roseli; Athayde, Natália Merten; Ferreira da Silva, Ana Marina Dutra; Brockhausen, Igor; Correia, Carolina da Cunha; Sobreira, Cláudia Ferreira da Rosa; Tomaselli, Pedro José; Petean, Flávio; de Oliveira, Rodrigo; Feitoza, Pablo Vinícius; et al. (Frontiers in Neurology, 2025)
IntroductionDifferential diagnosis of rare idiopathic inflammatory myopathies (IIM) is mainly based on clinical aspects, muscle biopsy analysis, and auxiliary assays that determine myositis-specific and associated autoantibodies (MSA and MAA). While MSAs are considered specific for their respective IIM subclass, MAAs can be present in more than one subclass and in other conditions. This study compares results of a multispecific line blot assay with the final diagnosis of IIM patients based on clinical features and muscle biopsy to draw conclusions for the test's applicability in the diagnostic workflow.MethodsSamples from patients (n = 50) diagnosed with various forms of IIM, including patients (n = 5) with other myopathies, were analyzed using the EUROLINE Autoimmune Inflammatory Myopathies 16 Ag (IgG), an anti-HMGCR (IgG) line blot, and the Anti-cN-1A ELISA (IgG, all EUROIMMUN).ResultsMSA and MAA were detected in 74.0% (37/50) of sera and were concordant with the final diagnosis in 64.8% (24/37), discordant in 16.2% (6/37) and not evaluable in 18.9% (7/37) of cases. In 100% (5/5) of patients with other myopathies, no MSA was found. MSA/MAA-co-positivity was observed in 18.0% (9/50) of patients. In 30.0% (15/50) of cases, the muscle biopsy analysis was essential to establish the final diagnosis.ConclusionThe agreement between serodiagnostic results and final diagnosis highlights the applicability of the EUROIMMUN myositis-related diagnostic test as first line diagnostic tool in the IIM diagnosis workflow and suggests morphological analysis in cases of inconclusive or negative serology. However, results of diagnostic assays shall always be interpreted in combination with clinical features.